SAFETY SYSTEM FOR LIQUEFIED PETROLEUM GAS (LPG) WITH MICROCONTOLLER BASED FUZZY DECISION TREE ALGORITHM - Yuda Irawan; Uci Rahmalisa; Refni Wahyuni; Hendry Fonda (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
The cause of the leak was caused by a hose that was no longer suitable for use in order to cause gas leakage that could have an effect on the LPG gas cylinder explosion. By making an alarm-and SMS-based LPG gas protection device with a MQ-6 sensor, users can see the leak in LPG gas. When this tool operates when a gas leak occurs, the MQ-6 has a leak in the LPG gas hose, so the alarm will sound. When active, the voice sends a command to Arduino to close the LPG gas valve. Then the alarm sends a command to the user via SMS to inform you that